2019
DOI: 10.7759/cureus.5096
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cardiologists in the Management of Systemic Lupus Erythematosus: First Reported Case of Three-vessel Disease in a Young Woman in Pakistan

Abstract: Systemic lupus erythematosus (SLE) is a multi-system autoimmune disorder with predilection towards young women. SLE is associated with increased risk of incidence of cardiac diseases which include atherosclerosis and coronary artery disease (CAD) that can present clinically as angina or myocardial infarction (MI) or be clinically silent in the initial stages. Furthermore, the use of corticosteroids for the treatment of SLE exacerbates the risk of thrombosis, possibly resulting in adverse cardiovascular events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in patients with SLE (4). Patients with SLE exhibit features of accelerated atherosclerosis and an increased risk of CAD that can be clinically silent in the initial stages, or angina or acute myocardial infarction (AMI) during disease progression (5). It has been reported that the risk of developing AMI is 2.67-10.00 times higher among patients with SLE compared with individuals without SLE (6).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in patients with SLE (4). Patients with SLE exhibit features of accelerated atherosclerosis and an increased risk of CAD that can be clinically silent in the initial stages, or angina or acute myocardial infarction (AMI) during disease progression (5). It has been reported that the risk of developing AMI is 2.67-10.00 times higher among patients with SLE compared with individuals without SLE (6).…”
Section: Introductionmentioning
confidence: 99%